2022
DOI: 10.1002/cncr.34435
|View full text |Cite
|
Sign up to set email alerts
|

Risk and tropism of central nervous system (CNS) metastases in patients with stage II and III cutaneous melanoma

Abstract: BACKGROUND:Recent data suggest that patients with stage III melanoma are at high risk for developing central nervous system (CNS) metastases. Because a subset of patients with stage II melanoma experiences worse survival outcomes than some patients with stage III disease, the authors investigated the risk of CNS metastasis in stage II melanoma to inform surveillance guidelines for this population. METHODS: The authors examined clinicopathologic data prospectively collected from 1054 patients who had cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, individuals with stage IIC melanoma had a significantly higher rate of isolated first recurrences in the CNS compared to those with stage III disease (12.1% vs. 3.6%, p = 0.002). The risk of ever developing brain metastases was elevated for patients with stage IIC, IIIB, and IIIC disease, with the highest risk observed in patients with stage IIID disease (HR, 8.59; 95%CI: 4.11–17.97) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, individuals with stage IIC melanoma had a significantly higher rate of isolated first recurrences in the CNS compared to those with stage III disease (12.1% vs. 3.6%, p = 0.002). The risk of ever developing brain metastases was elevated for patients with stage IIC, IIIB, and IIIC disease, with the highest risk observed in patients with stage IIID disease (HR, 8.59; 95%CI: 4.11–17.97) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, brain metastases have been associated with a poor prognosis, with median overall survival estimated to be approximately 4–6 months [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. More recent studies have reported an improvement in median overall survival from 14 months to 23 months for metastatic melanoma since the introduction of targeted therapies and immune checkpoint inhibitors [ 15 , 16 , 17 ]. The CheckMate 204 trial reported that the 3-year overall survival rate was 71.9% for patients with asymptomatic brain metastases who received ipilimumab plus nivolumab [ 18 ].…”
Section: Introductionmentioning
confidence: 99%